Qualitative study on the experiences of the Alzheimer caregiver: adaptation and impact - María Dolores Ruiz-Fernández; Rocío Ortiz Amo; Ángela María Ortega-Galán (Universidad de Alicante, 2019)
Objective: To deepen, through the experiences of family caregivers, what were the perceptions that caregivers had regarding the process of adaptation of Alzheimer's disease and the impact it had on their lives. Methodology: Two focus groups of caregivers of patients with Alzheimer-type dementia were formed, representative of the study population. Results: From the analysis of the discourses five dimensions or units of meaning emerged with fourteen subdimensions. These five dimensions are: knowledge about the illness, the caregiver's suffering, emotions, coping skills and the consequences in the life of the caregiver. Conclusion: We can determine that the adaptation to the role of caregiver of a person with Alzheimer's is conditioned by the mistaken beliefs or dysfunctional thoughts that arise in the caregiver, the emotions derived from the moral responsibility to assume the role of caregiver from the perspective of gender and, finally, the consequences of care during this period, the repercussions on their personal, family and work life.